Pemberdayaan Ibu Rumah Tangga Dalam Pemanfaatan Tanaman Obat Keluarga (TOGA) - Leswara, Dianita Febrina; Mufrod; Kurniasih, Kholif Sholehah Indra (The Journal of Innovation in Community Empowerment, 2024)
ABSTRACT. Indonesian have used plants as traditional medicine to treat health problems. In general, the use of traditional medicine is considered safer than the use of modern medicine. This is because traditional medicine has relatively fewer side effects than modern medicine. However, it is still necessary to use traditional medicines accurately to minimize side effects. Empowering housewives in using Family Medicinal Plants can be used to support improving family welfare and health. For this reason, this service activity aims to: (1) increase knowledge about the scientific properties of Family Medicinal Plants among housewives, (2) increase knowledge about the procedures for planting Family Medicinal Plants among housewives, and (3) improve skills for processing Family Medicinal Plants among housewives. stairs so that it can be beneficial for health. Service activities are carried out using the lecture method to explain the scientific benefits of Family Medicinal Plants, planting Family Medicinal Plants, and processing Family Medicinal Plants. Overall service activities can be said to be good and successful, seen from the success of the target number of training participants, achievement of training objectives, achievement of planned material targets, and participant's ability to master the material to meet predetermined targets. The Empowerment of Housewives in the Use of Family Medicinal Plants community service program in Pangkah Hamlet, Bantul, Yogyakarta was able to increase participants' interest and knowledge regarding the use of family medicinal plants. KEYWORDS: Herbal; Housewife; family medicinal plants